SINTESIS ETILENDIAMIDA DARI METIL ESTER MINYAK BIJI BINTARO (Cerbera manghas L.) MELALUI REAKSI AMIDASI DENGAN KATALIS NaOCH3 - Fath Ali Akbar; Daniel Daniel; Chairul Saleh (PROSIDING SEMINAR KIMIA, 2017)
Synthesis of ethylendimide from methyl ester of bintaro seed (Cerbera manghas L) through amidation reaction using NaOCH3 as catalyst have been done. Result of the sythesis have showed oil amount of bintaro seed are 50,36 % with acid value are 2,9192 mg KOH/g and free fatty acid are 1,4671 %. Oil of bintaro seed are converted to methyl ester using H2SO4 as catalyst for 5 hours in temperature 60-70 ºC in benzene which ratio of methanol and oil are 6:1 gave acid value are 21,4967 mg KOH/g and saponification value are 53,2352 mg KOH/g. Methyl ester of bintaro seed are reacterd with ethylendiamine and with NaOCH3 as catalyst. The result of amidation are viscous liquid and yellowish white color with acid value are 102,8435 mg KOH/g and saponification value are 33,7064 mg KOH/gram with HLB value are 13,446 which is higher than theoritically HLB value are 12,94. Analysis of FTIR showed ethylenediamide have formed which have proven by vibration of wave number at 1643,35 cm-1 for tetiary carbonyl amide group, 1056,99 cm-1 for ─C─N─ group and 3302,13 cm-1 for ─N─H─ group, but there are wave number appearance for ester carbonyl group at 1743,65 cm-1 which showed that methyl ester are not compeletely converted into ethylenediamide. Keywords: oil of bintaro seed, esterification, amidation, ethylenediamide